Star Formation History of the Local Group Dwarf Irregular Galaxy, NGC 6822 - Khatamsaz, F.; Abdollahi, M.; Abdollahi, H.; Javadi, A.; van Loon J. Th.
NGC 6822 is an isolated dwarf irregular galaxy in the local group at a distance of ∼ 490 kpc. In this paper, we present the star formation history (SFH) within a field with a radius of ∼ 3 kpc, beyond the optical body of the galaxy ( ∼ 1.2 kpc). We utilized a novel method based on evolved asymptotic giant branch (AGB) stars. We collected the Near-Infrared data of 329 variable stars, including long-period and -amplitude variables and Carbon-rich AGB stars. We used a stellar evolutionary track and theoretical isochrones to obtain the birth mass, age, and pulsation duration of the detected stars to calculate the star formation rate (SFR) and trace the SFH of the galaxy. We studied the history of galaxy star formation for the mean metallicity value of Z ≈ 0.003. We reconstructed the SFH for two regions: the bar region, a central rectangular area, and the outer region, which covers a circular field beyond the bar region and extends to a radius of 3 kpc. Our results show a significant burst of star formation around 2.6 and 2.9 Gyr ago in the bar and outer regions, respectively. Additionally, we observed a notable enhancement in the SFR in the bar region over the past 200 Myr.
Keywords: Stars